The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1111/j.1096-3642.1999.tb00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteology and systematic position of the Eocene salmonid †Eosalmo driftwoodensis Wilson from western North America

Abstract: The fossil salmonid tEosulmo dnzoodensis was originally described from fragmentary specimens. Study of new material of this fossil species confirms that it is a stem-group salmonine, with a mixture of primitive and derived salmonine features in its skull, but with its postcranial skeleton essentially of modern salmonine construction. Two autapomophies define the genus TEosalrno: a long anterodorsal process of the subopercle meeting the dorsal edge of the bone at an angle of about 60°, and a thin dermal basihya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 26 publications
(40 reference statements)
0
25
1
Order By: Relevance
“…An area of New Zealand, roughly centred on Rotorua-Taupo in the central North Island, was profoundly influenced by a series of relatively recent, and sometimes huge, volcanic eruptions lasting over ca. 50,000 years, the last major eruption being around 186 A.D. (Wilson and Walker 1985;Froggatt and Lowe 1990;Wilson and Houghton 1993). Substantial impacts on terrestrial biota have been described or postulated, and effects on freshwater biota are equally likely.…”
Section: Tasmania's Swamp Galaxias Galaxias Parvusmentioning
confidence: 95%
See 1 more Smart Citation
“…An area of New Zealand, roughly centred on Rotorua-Taupo in the central North Island, was profoundly influenced by a series of relatively recent, and sometimes huge, volcanic eruptions lasting over ca. 50,000 years, the last major eruption being around 186 A.D. (Wilson and Walker 1985;Froggatt and Lowe 1990;Wilson and Houghton 1993). Substantial impacts on terrestrial biota have been described or postulated, and effects on freshwater biota are equally likely.…”
Section: Tasmania's Swamp Galaxias Galaxias Parvusmentioning
confidence: 95%
“…Moreover, the shared evolutionary roots of galaxiids and salmonids must be very ancient, dating back at least to the mid-late Mesozoic. Fossils of recognisable salmonids and osmerids are known back to the upper Cretaceous to early Tertiary times (Romer 1966;Wilson and Williams 1991;Wilson and Li 1999), and even extant species of Oncorhynchus have been found in the Pliocene (Cavender and Miller 1972;Stearley and Smith 1993). Fossil galaxiids resembling extant species are known from the Miocene of New Zealand (McDowall 1976b;McDowall and Pole 1997;Lee et al submitted).…”
Section: Diseases and Parasitesmentioning
confidence: 99%
“…Based on morphological evidence, it has been suggested that Coregoninae is the sister group to the remainder of Salmonidae [3], [18], a finding that is corroborated by recent molecular investigation of some species of Salmonidae using nearly complete mitochondrial sequence data [14]. However, another recent phylogenetic study using a comprehensive set of nuclear genes suggests that Thymallinae may occupy that position [13], leaving uncertainties on the evolutionary relationship among subfamilies that has been widely accepted for decades.…”
Section: Introductionmentioning
confidence: 97%
“…It exhibits a range of morphological particularities (Fig. 1) among which the most evident are the elongated muzzle, small, fleshy mouth and the cranial bone convex in the orbital region (for a detailed morphological description see Karaman, 1927; Janković, 1961; Schöffmann, 1991; Stearley & Smith, 1993; Wilson & Li, 1999).…”
Section: Introductionmentioning
confidence: 99%